Anti-proliferative bioactivity against HT-29 colon cancer cells of a withanolides-rich extract from golden berry (Physalis peruviana L.) calyx investigated by Foodomics (2019)
A comprehensive Foodomics study was carried out in this work to investigate the changes induced at gene and metabolite expression levels on HT29 colon cancer cell lines upon treatment with a bioactives-enriched extract from goldenberry calyx. As a result of the proposed multi-omics approach, the tested extract induced transcriptional activation of pro-apoptotic genes, and altered the expression of several genes related to the oxidative stress response in treated cancer cells. Metabolomics data confirm altered cellular redox homeostasis, providing additional evidence to transcriptomic results. Foodomics data integration also revealed alteration on relevant metabolic processes, suggesting inactivation of aminoacyl tRNA charging pathway, dysfunction on carnitine shuttle and beta-oxidation of fatty acids, and pyrimidine ribonucleotide interconversion impairment. These observations are in line with functional analysis and anti-proliferative activity results, where the viability of HT-29 colon cancer cells was notably reduced after 48 h treatment without affecting the viability of normal human colon fibroblast cells.